Distribution of stream macroalgae in the northwest region of Sao Paulo State, southeastern Brazil - Necchi Júnior, O.; Branco, C. C.; Simao, R. C.; Branco, L. H. (Kluwer Academic Publ, 1995)
Forty-four stream segments were sampled from May to October in 1992 and 1993 in the northwest region of São Paulo State, southeastern Brazil (19 degrees 45'-21 degrees 25'S, 49 degrees 05'-51 degrees 30'S). Thirty-six macroalgal subgeneric taxa were found and Chlorophyta was the dominant algal group (47% species), followed by Cyanophyta (33.5%), Rhodophyta (14%) and Chrysophyta (5.5%). The most widespread species were Stigeoclonium helveticum (25% sites), Batrachospermum delicatulum and Compsopogon coeruleus (20.5%). Distribution was patchy, with species number per sampling site ranging from 0 to six (3.1 +/- 1.7) and correlated positively with species abundance. Species cover ranged from 0 to 61% of the stream bottom (19.1 +/- 19.7%). Most sites (57%) were dominated by one or two macroalgae species. No significant difference was found between the frequency distribution of variables measured for streams and for total macroalgae, but the most widespread species differed for most parameters and occurred over wider ranges of environmental conditions. Mean species number and abundance were close to values found in distinct regions or biomes of North America. Higher conductance and lower oxygen values, as well as rocky substrata, generally constituted the most favourable combination of conditions for the development of macroalgae in the region. The pattern of strong dominance of few species was considered to be typical for stream macroalgal communities in general.
Keywords: Batrachospermum delicatulum; Compsopogon coeruleus; Stigeoclonium helveticum; Chlorophyte; Chrysophyte; Cyanophyte; Geographic distribution; Macroalgae; Rhodophyte; Stream; Brazil, Sao Paulo State; North America